2019
DOI: 10.3389/fonc.2019.00687
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enhanced Recovery After Surgery on Postoperative Recovery for Pancreaticoduodenectomy: Pooled Analysis of Observational Study

Abstract: Purpose: To assess the impact of enhanced recovery after surgery (ERAS) protocols in pancreaticoduodenectomy. Methods: Four databases were searched for studies describing ERAS program in patients undergoing pancreatic surgery published up to May 01, 2018. Primary outcomes were mortality, readmission, reoperation and postoperative complications. Secondary outcomes were the length of stay and cost. Results: A total of 19 studies met inclusion and exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
1
26
0
1
Order By: Relevance
“…7 However, one more recent meta-analysis by Cao and his associates reported that ERAS reduced POPF rate, but had no influence on DGE rate. 8 The contradictory results might be related to their differences in inclusion criteria. The former enrolled the studies with only PD, while the latter included studies involving not only PD but also distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, one more recent meta-analysis by Cao and his associates reported that ERAS reduced POPF rate, but had no influence on DGE rate. 8 The contradictory results might be related to their differences in inclusion criteria. The former enrolled the studies with only PD, while the latter included studies involving not only PD but also distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, another meta-analysis analyzed 19 non-randomized comparative studies and reported opposite results. 8 Recently, several randomized controlled trials (RCTs) have been reported in evaluating the efficacy and safety of ERAS protocol in PD. [9][10][11] Herein, we conducted this systematic review and meta-analysis with the aim at further evaluating the impact of ERAS on postoperative outcomes after PD by collecting more nonrandomized comparative studies and RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced recovery after surgery (ERAS) is a series of effective perioperative interventions under the instruction of a multidisciplinary team, thus improving the surgical patients’ experiences both psychologically and physiologically [ 1 , 2 ]. Compared with the traditional perspective, the ERAS pathway is the new revolution for surgery, as it significantly decreases surgical complications, hospital stay, overall medical charges, and patient discomfort [ 3 , 4 , 5 ]. ERAS has a broad prospect of perioperative application, and an increasing number of surgery-related guidelines have been published in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of ERAS ® to the pancreatic surgeons armamentarium has certainly helped improve outcomes[ 26 , 27 ], especially reductions in overall and minor morbidity, incidences of delayed gastric emptying, incisional and intra-abdominal infections, and shortened length of stay, without increasing 30-d readmission and mortality[ 9 ]. It has been reported that up to 30% of patients are unable to receive adjuvant chemotherapy for pancreatic cancer for a variety of reasons[ 28 ].…”
Section: Discussionmentioning
confidence: 99%